Comorbidity of Obsessive-Compulsive Disorder and Schizotypal Personality Disorder: Clinical Response and Treatment Resistance to Pharmacotherapy in a 3-Year Follow-Up Naturalistic Study - Perris, Francesco; Fabrazzo, Michele; De Santis, Valeria; Luciano, Mario; Sampogna, Gaia; Fiorillo, Andrea; Catapano, Francesco (Frontiers in Psychiatry, 2019)
The present study aims to analyze the clinical and socio-demographic characteristics of patients with obsessive-compulsive disorder (OCD) in comorbidity with schizotypal personality disorder (SPD), as well as the response rate to pharmacological treatments. OCD+SPD patients had a younger age at onset, a higher probability to have more severe obsessive-compulsive symptoms, a higher rate of schizophrenia spectrum disorders in their first-degree relatives, and a poorer insight compared to OCD patients. During the 3-year follow-up period, these patients showed a lower rate of recovery, thus requiring augmentation with different psychotropic medications, including low doses of antipsychotics. Our findings suggest that the comorbidity of OCD and SPD causes a poor treatment response, and a reduced probability to recover using standard pharmacological treatment strategies. Further investigations are needed to identify alternative strategies, including psychoeducation and cognitive behavioral therapy, to manage such frequent comorbidity in clinical practice.